2019
DOI: 10.31557/apjcp.2019.20.8.2319
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of KRAS Codon 146 and FBXW7 Mutations in Thai Patients with Stage II-III Colon Cancer

Abstract: Background: KRAS, NRAS, and BRAF gene mutations are the most clinically relevant and frequently reported in colorectal cancer (CRC). Although data on these genes are frequently reported in several counties, data specific to these genes among Thai population are scarce. The aim of this study was to investigate and identify molecular alterations associated with colon cancer in Thai population, and to determine the impact of these genetic aberrations on clinical outcome. Methods:DNA from 108 archived formalin-fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Additionally, similar to the results of other authors [24,25] we noticed that mutations G12D and G12V are the most prevalent in the Serbian population. We found that the frequency of mutations in codons 59, 117 and 146 were 1.5%, which is in concordance with the study of Awidi et al [26] while a higher prevalence of the mutation in codon 146 was observed in patients from Thailand, where 8.3% of them had this mutation [27]. Many authors evaluated correlations between mutations in KRAS, age and sex of patients with clinicopathological characteristics of CRC and some of the results indicate that both tumor location and KRAS status play important roles in the prognosis of CRC patients [19,20,28].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, similar to the results of other authors [24,25] we noticed that mutations G12D and G12V are the most prevalent in the Serbian population. We found that the frequency of mutations in codons 59, 117 and 146 were 1.5%, which is in concordance with the study of Awidi et al [26] while a higher prevalence of the mutation in codon 146 was observed in patients from Thailand, where 8.3% of them had this mutation [27]. Many authors evaluated correlations between mutations in KRAS, age and sex of patients with clinicopathological characteristics of CRC and some of the results indicate that both tumor location and KRAS status play important roles in the prognosis of CRC patients [19,20,28].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies describe a more favorable clinical outcome in patients with CRC with a KRAS A146-mutated tumor upon anti-EGFR treatment compared with patients with tumors carrying another KRAS mutation. [54][55][56][57] Other studies show that tumors with a KRAS A146 mutation, like other KRAS mutations, are responsible for anti-EGFR resistance. [58][59][60][61] In this study, the homogenous population of initially unresectable liver-only metastatic CRC patients all receiving the same treatment regimen allowed for an unbiased comparison of the clinical features of patients harboring different KRAS tumor mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that missense mutations, SNP, and C>T mutations are the most common mutations in colon cancer. Former studies (33)(34)(35) have also confirmed that missense mutations are the most common type of colon cancer, and SNPs located in regulatory elements can affect the expression of coding genes through remote regulation, leading to cancer. We found that the four genes with the highest mutation frequency were APC, TP53, TTN, and KRAS, which is consistent with the results of previous studies (36).…”
Section: Discussionmentioning
confidence: 97%